細胞接着因子ギセリン/CD146の心筋細胞における発現制御機構の解析 - 弘瀬, 雅教; ハサン, アリフ ウル; 近藤, ゆき子; 佐藤, 幸子; 小原, 真美; 平, 英一 (日本薬理学会年会要旨集, 2023)
Gicerin / CD146 is a cell adhesion molecule which belongs to the immunoglobulin (Ig) superfamily. We have reported that gicerin / CD146 is involved in the hypertrophy of vessel neointima consists of smooth muscles. We speculate that gicerin / CD146 may also have some role in the hypertrophy of the cardiac muscle cells. In this study, we made a rat cardiac hypertrophy model by constricting the aorta (AAC, ascending aortic constriction) and examined the effect on the expression of gicerin / CD146. We confirmed the gene expression level of gicerin / CD146 was influenced by the AAC treatment. Next, stretch stimulation was applied to myocardial cell line H9c2 cells to confirm that gicerin / CD146 may participate in the cellular hypertrophy model. We also treated the cells with inhibitors MAP pathway enzymes. In cultured myocardial cells, the expression level of gicerin / CD146 was increased by the stretch stimulation and decreased by inhibiting the MAP pathway. Based on the above results, it was suggested that the expression of gicerin / CD146 is involved in cardiac hypertrophy, and that the MAP pathway may be involved in the expression of gicerin / CD146 RNA in the cardiomyocyte.